Investigation into the inter-lip characteristics of combined seals with double lips in different working conditions. (February 2023) - Peng, Chao; Miao, Jianming; Bauer, Niklas; Schmitz, Katharina
Abstract: Combined seals with double lips have the advantages of both the combined seals and the double lips, making them a popular choice in industrial applications. This paper proposed a numerical approach combining the finite element method and the mixed lubrication procedure. The conservation of fluid transport velocity and the update of inter-lip pressure are used to couple the characteristics of the two sealing lips. Simulations are conducted to analyze the performance of combined seals with double lips in different working conditions, including normal and differential working conditions, different velocities, and different roughness values. It is discovered that the inter-lip pressure helps support the seal and reduces the contact force. With the velocity increasing, the inter-lip pressure decreases, which increases friction.